2010
DOI: 10.1111/j.1464-410x.2010.09900.x
|View full text |Cite
|
Sign up to set email alerts
|

Do mixed histological features affect survival benefit from neoadjuvant platinum‐based combination chemotherapy in patients with locally advanced bladder cancer? A secondary analysis of Southwest Oncology Group‐Directed Intergroup Study (S8710)

Abstract: and for patients with mixed tumours, with adjustment for age and clinical stage. RESULTS• There was evidence of a survival benefit from chemotherapy in patients with mixed tumours (hazard ratio 0.46; 95% CI 0.25-0.87; P = 0.02). Patients with pure UC had improved survival on the chemotherapy arm but the survival benefit was not statistically significant (hazard ratio 0.90; 95% CI 0.67-1.21; P = 0.48).• There was marginal evidence that the survival benefit of chemotherapy in patients with mixed tumours was grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 14 publications
2
72
0
1
Order By: Relevance
“…Conversely, patients with positive soft tissue margins and SqD may still benefit from platinum based chemotherapy, which has proven effective for urothelial carcinoma with mixed features, and suggests possible differences in molecular pathways for metastases in pure SCC. 20 Our findings must be interpreted in the context of the study design. This study is retrospective, and our results are limited by unmeasured factors affecting selection into treatment and confounding the associations between tumor characteristics and outcomes.…”
Section: Discussionmentioning
confidence: 92%
“…Conversely, patients with positive soft tissue margins and SqD may still benefit from platinum based chemotherapy, which has proven effective for urothelial carcinoma with mixed features, and suggests possible differences in molecular pathways for metastases in pure SCC. 20 Our findings must be interpreted in the context of the study design. This study is retrospective, and our results are limited by unmeasured factors affecting selection into treatment and confounding the associations between tumor characteristics and outcomes.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, Kastritis et al found that when treating advanced or metastatic urothelial carcinoma with a platinum-based chemotherapy regimen, SQD and NV bladder cancer exhibited similar responsiveness 16 . Lastly, in a secondary analysis of the SWOG S8710 clinical trial using neoadjuvant MVAC (methotrexate, vincristine, doxorubicin, and cisplatin), SQD demonstrated nonstatistically significant (p=0.09) improved survival benefit compared to NV in locally advanced urothelial carcinoma 14 . In our cohort, patients receiving neoadjuvant chemotherapy responded at similar rates although we are significantly underpowered to fully evaluate this.…”
Section: Discussionmentioning
confidence: 97%
“…While recent studies have found certain variants such as micropapillary and plasmacytoid to act more aggressively, SQD has been historically described to act similarly to NV histology 5,11,14,15,18,19 . However, much of the SQD literature draws on older cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Les variants les plus fréquents sont les carcinomes urothéliaux avec inflexions épidermoïdes ou adénocarcinomateuses. Dans l'essai du SWOG, la présence de ces variants a même été décrite comme une variable plutôt favorable pour l'obtention d'une RCP [16]. Les carcinomes non urothéliaux (10 % des cancers de la vessie) comprennent les adénocarcinomes, dont les carcinomes de l'ouraque, les carcinomes épidermoïdes, les carcinomes neuroendocrines à petites cellules et les sarcomes primitifs de la vessie.…”
Section: Variants Urothéliaux Et Histologies Non Urothélialesunclassified